1999
DOI: 10.1007/s11661-999-0022-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of softened regions in weld heat-affected zones of 6061-T6 aluminum alloy—Characterizing of the laser beam welding process

Abstract: In welding 6061-T6 aluminum alloy, softening caused by the dissolution of strengthening ␤ Љ (Mg 2 Si) precipitates occurs in heat-affected zones (HAZs). Laser beam welding is advantageous in view of narrower softened regions. The width of the softened region in a laser beam weld with a welding speed of 133 mm/s is 1/7 that of a tungsten inert gas (TIG) weld with a speed of 5 mm/s. The hardness distributions and width of softened regions in the HAZ have been quantitatively predicted to characterize the laser be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 7 publications
3
11
0
4
Order By: Relevance
“…As a result, tensile failure is obtained in the FZ. The hardness drop in the HAZ of the GTA weld is caused by insufficient strengthening in the matrix of this region due to precipitation of non-hardening phases during weld thermal cycle [25].…”
Section: Resultsmentioning
confidence: 99%
“…As a result, tensile failure is obtained in the FZ. The hardness drop in the HAZ of the GTA weld is caused by insufficient strengthening in the matrix of this region due to precipitation of non-hardening phases during weld thermal cycle [25].…”
Section: Resultsmentioning
confidence: 99%
“…Hirose et al [9,10] measured the widths of the softened region in the HAZ of CO 2 laser -welded 6061-T6 sheet material of 1-mm thickness. The softened region is defined as the region where hardness values fall below 90% those of the base metal.…”
Section: Heat Affected Zonementioning
confidence: 99%
“…Their results showed that the widths of softened regions in the HAZs of the laser welds are of the order of one seventh to one quarter those for TIG welds. [9,10] Although the HAZs of laser-welded joints are very narrow, many solid-state reactions such as grain growth and precipitate coarsening may occur in the zone. [11] In non -heat-treatable Al alloy, softening occurs because of localized annealing in the HAZ by grain growth or loss of strain-hardened structure.…”
Section: Heat Affected Zonementioning
confidence: 99%
“…However, the hardness of heat-affected zone (HAZ) was decreased to 80 HV. It has been reported that during surface melting of AA6061-T6 aluminum, strengthening Mg 2 Si precipitates formed by T6 solution-aging heat treatment on 6061 aluminum dissolve in the aluminum matrix in the heat-affected zone [30,31]. Figure 10 shows the hardness maps along the polished top surface of the as-alloyed and re-melted layers.…”
Section: Microstructural and Phase Analysismentioning
confidence: 99%